Unraveling the complexities of early-onset colorectal cancer: a perspective on dietary and microbial influences - Atchade, Axelle Mayode; Williams, Jennie L.; Mermelstein, Linda; Nemesure, Barbara (Frontiers in Public Health, 2024)
While advances in screening have resulted in declining rates of colorectal cancer (CRC) among adults ≥50 years of age since the mid-2000s, the incidence of early-onset CRC (EOCRC) has steadily increased over the last decade. This increase is not fully accounted for by hereditary factors, and the hypothesis that a sedentary lifestyle and obesity are the primary culprits is not fully supported by recent reports indicating that many affected individuals lead active lifestyles, maintain normal weight, and are otherwise healthy. Attention has shifted toward dietary patterns, notably the consumption of processed and ultra-processed foods found in Western diets, which are suspected of disrupting the gut microbiome balance that potentially leads to EOCRC. The impact of antibiotic use on the gut microbiome is also posited as a contributing factor, given its rising prevalence in medical and agricultural practices. We propose that a paradigm shift is necessary for EOCRC research, moving beyond metabolic factors to a broader exploration of dietary and microbial influences. Future research must prioritize understanding the relationship between dietary habits, particularly processed food intake, antibiotic exposure, and gut microbiome dynamics, to unravel the complex etiology of EOCRC. This will be crucial in developing comprehensive preventive strategies to address the increasing incidence of this malignancy in younger populations.